The Bobwhite Quail of Crane Naval Ammunition Depot, Indiana - 25 Years of Protection and Plant Succession - Thomas W. Hoekstra; Charles M. Kirkpatrick (National Quail Symposium Proceedings, 2017)
A low-density bobwhite quail population was studied to determine its status after 25 years of plant succession ·and protection from hunting on Crane Naval Anununition Depot. The summer breeding population on the study area was approximately one-fifth of that around the periphery of CNAD. The winter population was approximately 1 bird per 50 acres. The subadult to adult ratio was normal (83: 17) but the corresponding sex ratio of 60M:40F was unbalanced. Coveys retained their identity and, with the exception of 1 covey, maintained their numbers during winter. The major habitat limitation occurred during the nesting and brooding season. The low density of bobwhites was concluded to be primarily the combined result of poor nesting cover and above-normal loss of mature females during the breeding season.